High power factor dimmable electronic ballast for multiple tubular fluorescent lamps - Wakabayashi, F. T.; de Oliveira, RAN; Canesin, C. A. (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This paper presents a dimmable electronic ballast designed for multiple fluorescent lamps applications. A ZCS-PWM Boost rectifier and a classical resonant Full-Bridge inverter compose this new electronic ballast, providing conditions for the obtaining of high input power-factor, and soft-switching processes for all semiconductor devices employed in the structure. The instantaneous average input current control technique is employed in the Boost rectifier. Concerning the Full-Bridge inverter, it is controlled by the imposition of phase-shift in the current processed through the sets of resonant filters + lamps, according to an adaptation in a specially designed control IC, called IR2159. Experimental results are presented in order to validate the analyses developed in this paper.
Keywords: fluorescent lamps; power factor